30. THE IMPORTANCE OF PIPELINE TRANSPORT IN THE DEVELOPMENT OF SOCIAL RELATIONS - Salimov Bakhriddin Lutfullaevich. Sadullaeva Malika Azamatovna (Innovative technologies in construction Scientific Journal, 2023)
In the article, it is analyzed that the development of pipeline transport is one of the important factors for improving social relations along with work that ensures the sustainable functioning of the economy of our country, and the reason for this is that pipeline transport costs very little, and labor productivity is much higher, and accordingly, the income is at a high level done